Africa's glorious legacy - Time-Life Books (1994)
Looks at the ancient civilizations of Zimbabwe, Nubia, West Africa, and Benin.
Includes biblographical references (pages 161-164) and index.
Accelerated Reader AR
Keywords: Excavations (Archaeology) -- Africa; Africa -- Antiquities; Africa -- Civilization